2019
DOI: 10.3389/fgene.2019.00761
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Fetuses With Increased Nuchal Translucency by Genome Sequencing Analysis

Abstract: Background: Increased nuchal translucency (NT) is an important biomarker associated with increased risk of fetal structural anomalies. It is known to be contributed by a wide range of genetic etiologies from single-nucleotide variants to those affecting millions of base pairs. Currently, prenatal diagnosis is routinely performed by karyotyping and chromosomal microarray analysis (CMA); however, both of them have limited resolution. The diversity of the genetic etiologies warrants an integrated assay… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 45 publications
2
64
1
Order By: Relevance
“…Indeed, in our cohorts, 22 fetuses referred for CMA did not undergo serum screening or NIPS, and this resulted in 6 (27.3%) fetuses with trisomy 21/18/13 still being identified during GS implementation. We also note that the prenatal detection rate for P/LP SNVs/INDELs in our study was lower than that in a previous study of 50 fetuses with increased nuchal translucency (11.7% vs 14%) [18], possibly due to our larger cohort and the broader range of fetal structural anomalies in our study. However, the incremental diagnostic yield of ES in CMAnegative cases was higher in this study (12.7% vs 8.5%-10%) [8,9] than in previous prospective studies on the prenatal application of ES in fetuses with structural or growth anomalies who had normal CMA results.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Indeed, in our cohorts, 22 fetuses referred for CMA did not undergo serum screening or NIPS, and this resulted in 6 (27.3%) fetuses with trisomy 21/18/13 still being identified during GS implementation. We also note that the prenatal detection rate for P/LP SNVs/INDELs in our study was lower than that in a previous study of 50 fetuses with increased nuchal translucency (11.7% vs 14%) [18], possibly due to our larger cohort and the broader range of fetal structural anomalies in our study. However, the incremental diagnostic yield of ES in CMAnegative cases was higher in this study (12.7% vs 8.5%-10%) [8,9] than in previous prospective studies on the prenatal application of ES in fetuses with structural or growth anomalies who had normal CMA results.…”
Section: Discussioncontrasting
confidence: 88%
“…Talkowski et al [17] identified precise translocation breakpoints that directly disrupted CHD7 and LMBRD1 by using ~12-fold GS in an undiagnosed prenatal sample, and this finding could not have been reliably inferred from conventional karyotyping. Choy et al [18] demonstrated that 30-fold GS could provide a two-fold increase in diagnostic yield (32.0%, 16/50) in fetuses with increased nuchal translucency (≥3.5 mm) compared with routine CMA and/or karyotyping (16.0%, 8/50). The additional diagnoses by GS include 7 (14%, 7/50) cases with pathogenic or likely pathogenic (P/LP) SNVs/INDELs, and their result demonstrated the potential of GS to replace the combination of CMA and ES in prenatal diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] A recent study had also showed the feasibility of applying genome sequencing (GS) for prenatal diagnosis of fetuses with increased NT for comprehensive detection of various disease-causing genomic variants. 26 However, accurate prenatal diagnosis of skeletal dysplasia by invasive procedures is still under debate in the absence of a relevant family history, and the time from invasive testing to diagnosis can be lengthy. 12 On the other hand, the cost of WES and WGS is relatively high and clinical utility of these technologies in prenatal diagnosis is to be addressed by large-cohort prospective studies.…”
Section: Clinical Utility Of Nips-mmentioning
confidence: 99%
“…Chromosomal abnormalities affect one of 150 live births, and the prevalence is even higher in pregnancies [ 1 , 2 ]. Prenatal diagnosis of chromosomal abnormalities can be performed by using advanced technologies such as chromosomal microarray analysis (CMA) and genome sequencing [ 3 , 4 ], which, however, requires an invasive procedure such as amniocentesis or chorionic villi sampling (CVS) to obtain a fetal sample for testing. These procedures carry a 0.1–0.2% procedure-related miscarriage risk [ 5 ].…”
Section: Introductionmentioning
confidence: 99%